Contemporary trends in cardiogenic shock: Incidence, intra-aortic balloon pump utilisation and outcomes from the London Heart Attack Group. Issue 1 (1st February 2018) - Rathod, Krishnaraj S; Koganti, Sudheer; Iqbal, M Bilal; Jain, Ajay K; Kalra, Sundeep S; Astroulakis, Zoe; Lim, Pitt; Rakhit, Roby; Dalby, Miles C; Lockie, Tim; Malik, Iqbal S; Knight, Charles J; et al.
Abstract: Background: Cardiogenic shock remains a major cause of morbidity and mortality in patients with ST-segment elevation myocardial infarction. We aimed to assess the current trends in cardiogenic shock management, looking specifically at the incidence, use of intra-aortic balloon pump therapy and outcomes in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention. Methods and results: We undertook an observational cohort study of 21, 210 ST-segment elevation myocardial infarction patients treated between 2005–2015 at the eight Heart Attack Centres in London, UK. Patients' details were recorded at the time of the procedure into local databases using the British Cardiac Intervention Society percutaneous coronary intervention dataset. There were 1890 patients who presented with cardiogenic shock. The primary outcome was all-cause mortality at a median follow-up of 4.1 years (interquartile range: 2.2–5.8 years). Increasing rates of cardiogenic shock were seen over the course of the study with consistently high mortality rates of 45–70%. A total of 685 patients underwent intra-aortic balloon pump insertion during primary percutaneous coronary intervention for cardiogenic shock with decreasing rates over time. Those patients undergoing intra-aortic balloon pump therapy were younger, more likely to have poor left ventricular function and less likely to have had previous percutaneous coronary intervention compared to the control group. Procedural success rates were similar (86.0% vs 87.1%, p =0.292) although crude, in-hospital major adverse cardiac event rates were higher (43.8% vs 33.7%, p <0.0001) in patients undergoing intra-aortic balloon pump therapy. Kaplan-Meier analysis demonstrated significantly higher mortality rates in patients receiving intra-aortic balloon pump therapy (50.9% intra-aortic balloon pump vs 39.9% control, p <0.0001) during the follow-up period. After multivariate Cox analysis (hazard ratio 1.04, 95% confidence interval 0.62–1.89) and the use of propensity matching (hazard ratio: 1.29, 95% confidence interval: 0.68–1.45) intra-aortic balloon pump therapy was not associated with mortality. Conclusion: Cardiogenic shock treated by percutaneous coronary intervention is increasing in incidence and remains a condition associated with high mortality and limited treatment options. Intra-aortic balloon pump therapy was not associated with a long-term survival benefit in this cohort and may be associated with increased early morbidity.